Striking Patterns: Contemporary Ikat Design and Its Future. (3rd July 2019) - de Jong, Willemijn; Kunz, Richard
Abstract: This review presents the results of a conference on ikat textiles organized in the context of the exhibition Striking Patterns: Global Traces in Local Ikat Fashion at the Museum der Kulturen Basel, Switzerland (October 2016 to March 2017). Academics and professional experts, some of them working for NGOs, debated often neglected potentialities as well as the future of contemporary ikat design and other intricately patterned handwoven textiles: the significance of new patterns; intellectual property rights; and educational encouragement. The general focus lay on the controversially perceived innovation of textile patterns in Indonesia and Timor-Leste. We will here present the main arguments of the discussion and our own suggestions for further research.